AGRONOMIC AND ECONOMIC EFFECTIVENESS OF Zn, Cu, B MICROFERTILIZERS ON THE GROWTH AND YIELD OF TOMATO PLANTS (Solanum lycopersicum) - Furqoni, Hafith (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Micronutrient fertilizers containing zinc (Zn), copper (Cu), and boron (B) play an important role in supporting the growth and yield of tomato plants. This study aimed to evaluate the agronomic and economic effectiveness of micronutrient fertilizer application on tomato growth, yield, and farming feasibility. The experiment was conducted with six treatment levels of micronutrient fertilizer doses (0, 0.5, 0.75, 1.0, 1.25, and 1.5 doses). The study used a randomized complete block design. Data were statistically analyzed using analysis of variance and the Duncan Multiple Range Test (DMRT) at a 5% significance level. Farming analysis was conducted using economic calculations with profit and R/C ratio as variables. The results showed that micronutrient fertilizer application significantly affected plant height, number of branches, and number of flower clusters, as well as yield components such as number of fruits per plant, fruit weight, and total yield per plant, plot, and hectare. The 1.0 dose treatment showed the best results with 125.8 fruits per plant, a yield of 2,346.5 g per plant, and 15.79 tons per hectare. Agronomic effectiveness was measured using the relative agronomic effectiveness (RAE) value, where the 1.0 dose treatment showed the highest value of 199%, indicating a 1.99-fold increase in yield compared to the control. Economically, this treatment also resulted in the highest profit of Rp14,075,000 with the highest R/C ratio. These results indicate that Zn, Cu, and B micronutrient fertilizers are not only effective in increasing tomato productivity but also economically feasible for implementation in tomato farming.